Knowledge Organization Capability and Competitiveness of Chartered Public Universities in Kenya - Gachanja, Joseph; Deya, Jared; Muturi, Willy (European Journal of Business and Strategic Management, 2024)
Purpose: Knowledge has increasingly become one of the most critical determining factors for organizational competitiveness. In order to acquire and sustain a competitive advantage, it is vital for an organization to develop effective strategies that foster knowledge creation, transfer and integration in the performance of the organization. Knowledge organization refers to activities such as document description, indexing, and classification that provide systems of representation and order for information and knowledge materials. The purpose of this study was to establish the relationship between knowledge organization capability and competitiveness of chartered public universities in Kenya. Methodology: The study adopted a descriptive design. The population of the research consisted of 31 chartered public universities authorized to operate in Kenya as at December 2020. The study adopted a census methodology while purposeful and convenient sampling was adopted to select respondents amongst the middle level management staff. The study used both secondary and primary data. A self-administered questionnaire was used as the primary data collection instrument. Out of 155 questionnaires that were sent out, 123 were filled and returned. Statistical Package for Social Studies (SPSS) was used for data analysis. The study used regression model to estimate the level of significance which yielded a positive and significant influence of knowledge organization capability on competitiveness of chartered public universities in Kenya. Findings: The findings indicate that organizational initiatives such as effective knowledge collaboration and utilization, deployment of information technology systems that support knowledge organisation and easy access to information and data contribute to a healthy environment conducive for knowledge management. Owing to the foregoing, the study concluded that knowledge organization capability had a significant positive impact on competitiveness of chartered public universities. Unique Contribution to Theory, Practice and Policy: The study recommended that public universities needed to embrace knowledge organization capability in order to obtain sustainable competitive advantage.